Shifts in Chinese Dining Consumption Habits after the COVID-19 Pandemic and Future Trends in the Catering Industry - Dingova, Vendula (2025)
This study explores the significant changes in China's catering industry after the COVID-19 pandemic. The pandemic sped up the digitalization of the catering industry and changed consumers' eating habits. Consumers now place greater emphasis on value for money while also pursuing high quality, and they have an unprecedented focus on food safety and hygiene. Online food delivery has transformed from an emergency option during the pandemic to a mainstream daily dining option, with significant growth in both market size and user numbers. Pre-prepared meals have also become increasingly popular among catering companies due to their standardization and cost-effectiveness. These changes have collectively driven a profound transformation in the production, distribution, and consumption patterns of the catering industry.